Factors associated with the use of dental health services in primary care in northeastern Mexico. - Guillermo Cruz; Georgina Núñez; Ana Salinas; Esteban Ramos; Rosa Sánchez (Universidad de Concepción., 2016)
In Mexico, as in many other Latin American countries, the use of dental health services (UDHS) has been scarcely studied, especially the one related with groups that are considered at risk in certain areas. The aim of this study was to evaluate the factors associated with UDHS in an at risk population in primary care. Material and Methods: Cross-sectional study, involving students (T), pregnant women (PW), workers (W) and older adults (OA) (n=368). Variables such as the use of dental health services and factors such as geographical, economic, and organizational barriers were measured. Descriptive statistics, Chi Square test and multivariate binary logistic regression analysis were used. Results: 40.2% (95% CI 30.2-50.2) of the W group had a history of UDHS in primary care, 20% (95% CI 11.8-28.2) of the PW group had spent more than a year without visiting the dentist and 33% (95% CI 23.7-43.9) had been treated at a private dental care service. Level of schooling, occupation, federal support from "Programa Oportunidades" and access to dental care services (p<0.01) were factors associated with UDHS, independent of potential confounders. Conclusion: The health system should guarantee health care by offering comprehensive dental health services and removing organizational barriers to promote a more equitable access to dental care.